THE QURANIC STORY OF MARY: DOES RETHINKING THE TEXT SUPPORT WOMEN PROPHETHOOD? - Hasan, Abla (UIN Ar-Raniry, 2016)
Women prophethood has always been an alien concept to Islamic theology. According to modern as well as mediaeval mainstream Islamic schools of exegeses, jurisprudence and even according to everyday schools of fatwa: women are either too inferior, too week, or even not pure enough to meet the requirements or handle the challenges associated with prophethood. However, rethinking the Quranic text, in isolation from mediaeval gender biased narrow preferences, proves this view to be wrong. In this paper I provide a unique linguistic analysis of the Quranic story of Maryam, the mother of Jesus and the only woman mentioned by name in Quran. Maryam as I argue, is acknowledged in Quran as a female prophet: chosen equally to all chosen men, i.e., male prophets and above all women. In addition, a logical analysis in favor of MaryamÃ¢â‚¬â„¢s prophethood will be provided. The juxtaposition of both evidence supports women prophethood.Ã‚Â